Asparaginase untuk Terapi Leukemia Limfoblastik Akut pada Anak: Analisis - Lawrenti, Hastarita (Cermin Dunia Kedokteran, 2025)
Acute lymphoblastic leukemia (ALL) is the most frequently diagnosed childhood malignancy. The five-year survival rate in high-income countries is higher than in low-income countries. Asparaginase remains the cornerstone of treatment in childhood ALL. There are several types of asparaginase available worldwide, including native E. coli asparaginase, pegasparaginase, Erwinia asparaginase, calaspargase pegol, and recombinant Erwinia asparaginase. Hypersensitivity reactions are the main complication related to asparaginase. The other concern is the development of anti-asparaginase antibodies which results in silent inactivation with no therapy benefit. Therapeutic drug monitoring is required in pediatric patients with ALL undergoing asparaginase therapy.